Formulation of photovoltaic inverter weighted conversion efficiency for equatorial climate - Ab. Rahman, Azhan (2021)
The system energy yield (Esys) is a performance indicator used by the installer to predict the energy output generated by a photovoltaic (PV) system. From the Esys estimation, the return of investment (ROI) for the installation can be approximated. The Esys equation consists of several elements, in which one of them is the PV inverter efficiency. The peak or maximum efficiency (ηmax) value from the inverter data sheet is usually used, but this practice is inaccurate because the PV inverters rarely operate at the peak power. Alternatively, the weighted efficiency is more preferable as it essentially considers the power conversion characteristics of the inverter when subjected to varying solar irradiance. Currently, the European weighted efficiency (ηEURO) is the most recognized and widely accepted. This is because, historically, European countries (particularly Germany) used to be the largest exporter and consumer of PV inverters throughout the world. Since ηEURO is developed based on a specific European irradiance profile, it is suspected that its value may not be suitable for inverters installed in different climatic conditions, particularly the equatorial region. Thus, the first objective of this work is carried out to prove this hypothesis. A one-year dataset from a weather station located at Universiti Teknikal Malaysia Melaka is collected with adherence to the IEC 61724 Standard. This irradiance profile is injected into a PV array simulator (PVAS) and tested on four PV inverters with different sizes and technologies. It is found that the recalculated ηEURO does not conform to the value stated in the respective inverter’s datasheet, thus confirming the above hypothesis. This finding inspires the formulation of a new weighted efficiency formula for the equatorial climate (ηEQUA). Three methods have been utilized, namely the IEC 61683 Standard, Response Surface Methodology (RSM) and Equatorial Irradiance-Duration Curve. The outcomes revealed that the last approach is the most practical solution to formulate ηEQUA. The newly developed formula is validated by the measured data from the field. It is demonstrated that the prediction of Esys using ηEQUA closely matched the Esys of a real 3 kW PV system, with only 0.16% difference between the two. It is envisaged that the usage of ηEQUA instead of ηmax (or ηEURO) will results in more accurate Esys and ROI predictions for PV system installed in the equatorial region.